INSENTIF DAN HONOR GURU NON PNS, DAN MEKANISME PENGADAAN UPTD DAN DIKLAT BAGI GURU DAN KEPALA SEKOLAH BERDASARKAN UNDANG-UNDANG NO 23 TAHUN 2014 - Amiruddin, Amiruddin; Chaniago, Nasrul Syakur (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Regarding SOTK, the government has regulated it through Law Number 23 of 2014, PP Number 18 of 2016 and governor regulations.. For work support units for the Education Office of North Sumatra Province, the UPTD was established as the representative of the Provincial government in the Regency/City. There will be no problem with the appointment of honorary teachers at the central or regional levels. It turns out that the biggest problem lies in the appointment of honorary teachers who are appointed by schools related to their salary and incentive allowances. Switched from schools or districts/cities and is now delegated to North Sumatra Province.To deal with the problem of low teacher UKG, the government also has enormous homework to make teachers become professional, productive and creative, so readiness is needed from various things, including costs and human resources who are able to provide guidance and direction. Keywords:Law No 23 of 2014, Incentives